2017
DOI: 10.1038/bjc.2017.140
|View full text |Cite
|
Sign up to set email alerts
|

Stroma-regulated HMGA2 is an independent prognostic marker in PDAC and AAC

Abstract: Background:The HMGA2 protein has experimentally been linked to EMT and cancer stemness. Recent studies imply that tumour–stroma interactions regulate these features and thereby contribute to tumour aggressiveness.Methods:We analysed 253 cases of pancreatic ductal adenocarcinoma (PDAC) and 155 cases of ampullary adenocarcinoma (AAC) for HMGA2 expression by IHC. The data were correlated with stroma abundance and supplemented by experimental studies.Results:HMGA2 acts as an independent prognostic marker associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 65 publications
7
31
0
Order By: Relevance
“…In fact, our recent single molecule study revealed that HMGA2 can stabilize hairpins that are formed in single stranded DNA regions (28). In this context, it is noteworthy that our data correlates with a recent extensive in vivo study that implicates HMGA2 expression as a prognostic factor to poor clinical outcomes in human pancreatic cancer patients treated with DNA synthesis inhibitors (58).…”
Section: Discussionsupporting
confidence: 84%
“…In fact, our recent single molecule study revealed that HMGA2 can stabilize hairpins that are formed in single stranded DNA regions (28). In this context, it is noteworthy that our data correlates with a recent extensive in vivo study that implicates HMGA2 expression as a prognostic factor to poor clinical outcomes in human pancreatic cancer patients treated with DNA synthesis inhibitors (58).…”
Section: Discussionsupporting
confidence: 84%
“…To investigate whether knockdown of ITGA5 in hPSCs retards their pro-tumorigenic effects in vivo, we established a co-injection tumor model in immunodeficient SCID mice. As consistent with previous reports 12,30 , tumors derived from co-injection of PANC-1 and hPSCs showed a significant increased tumor growth compared to tumors with PANC-1 cells alone ( Fig. 4D).…”
Section: Itga5 Knockdown Inhibits Psc-induced Paracrine Effect In Vitsupporting
confidence: 92%
“…These results suggest that HMGA2 acts as a target gene of many micro RNAs (miRNAs) and lncRNAs, which play critical roles in regulating tumorigenesis and cancer progression. In addition, several recent studies demonstrated that HMGA2 overexpression, both in the tissues and blood of patients with cancer correlated with poor tumor differentiation, positive lymph node metastasis, and advanced stage, indicating a poor prognosis [ 46 , 47 ]. As a member of the HMGA protein family, HMGA1 also has been reported to be overexpressed in cancers and promote tumorigenesis [ 48 51 ].…”
Section: Discussionmentioning
confidence: 99%